Pengelolaan Perikanan Cakalang yang Didaratkan di Pelabuhan Perikanan Nusantara (PPN) Prigi, Trenggalek: Aplikasi Feedback Harvest Control Rule : Fishery management of Skip jack tuna landed in Prigi Fishing Port, Trenggalek: Feedback Harvest Control Rule Application - Ledhyane Ika Harlyan; Wahida Kartika Sari; Farisa Mardiana Rahma; Fuad Fuad; Muhammad Arif Rahman (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
Cakalang (Katsuwonus pelamis) is one of the leading export commodities landed at the Prigi Fishing Port (PPN Prigi). Skipjack tuna fisheries management conducted the conventional single-species Schaefer model which is often applied although it is not technically suitable for multispecies fishery. The application of feedback harvest control rule (HCR) is an alternative harvest strategy that has been successfully implemented and validated for multispecies fishery. This study estimated allowable biological catch by applying two harvest strategies, HCR feedback and Schaefer surplus production model using catch-effort data of skipjack tuna landed at PPN Prigi in the period 2010 - 2019. Model Schaefer pointed out that catches have exceeded the maximum sustainable yield () even employed low the fishing effort which was under the fishing mortality consistent with achieving MSY (). The application of feedback HCR that has been previously validated can be an alternative of harvest strategy for use in fisheries where only mixed species data is available. Key words: multispecies fishery, harvest strategy, Schaefer model, maximum sustainable yield, single-species approach